Penerapan Pipa Paralon Dalam Teknologi Tepat Guna Sebagai Sarana Alat Bantu Sebar Pupuk Tanaman Jagung - Riena Fitri Andhita S; Taufikurrahman Taufikurrahman; Dharma Putra Raharja; Mohammad Kafi Putra Jauhari; Nabila Ayu Kristina; Abid Abhirama (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Appropriate Technology is a technology designed for a particular society so that it can be adapted to the environmental, ethical, cultural, social, political and economic aspects of the community concerned. An example of the application of appropriate technology or TTG is a paralon pipe as a means of distributing fertilizer for corn plants. The purpose of the design of Appropriate Technology in the form of a corn fertilization tool is to assist the task of farmers in giving fertilizer to corn so that it can shorten the estimated time and be more evenly distributed. The object of this journal is a group of farmers in Mentor Village. With this innovation, a tool to fertilize corn plants from a paralon pipe allows farmers to use this tool to make it easier and more practical for farmers in the fertilization process. The tools used have also been designed with the existing soil structure so that if the soil is wet the tool will not sink and can be used according to the existing weather. Therefore, the author consulted with the farmer group so that the end of the pipe was lengthened in order to adjust the soil conditions in Mentor village.